Anthropocene – humankind as global actor: Insights into historic and current perspectives - Allerberger, Franziska; Stötter, Johann (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
By proclaiming a new geological epoch in which humankind has become a dominant global driver and force of Earth system processes, Crutzen and Stoermer have triggered heated and unexpected debates among the scientific community in 2000. Yet, limiting the Anthropocene to a geological-stratigraphically defined time unit is highly questionable – if not absurd – as already in the 19th century scientists have dealt with the interaction of mind and matter with respect to the actions of humans and their impacts on the environment. Against this background, the article firstly provides an overview of historical concepts addressing humankind as global actor, whereby the differentiation and interplay between mind and matter is explicitly considered. Secondly, several characteristics of the Anthropocene are outlined but without claiming completeness. These considerations lead us to questions regarding the consequences of the Anthropocene as a “diagnosis of present times [Gegenwartsdiagnose]” (Horn and Bergthaller 2019: 12) for science itself, which are discussed in more detail in our second contribution in this Special Issue.